Organizational justice among teachers: a case of boarding schools of Tikapur Municipality - Kandel, Damodar (Journal of Tikapur Multiple Campus, 2017)
This study is designed to explore the organizational commitment and job performance as the driver for organizational justice. Questionnaires were distributed to 49 teachers from 13 boarding schools located in Tikapur Municipality. Majority of the respondents (67.5%) falls in the category of Intermediate level, about 32.5% respondents were form the bachelor level and 67.53% respondents were male and about 32.5 % respondents were female. Descriptive statistics and correlation were used to analysis the data. Using correlation and regression equation, organizational commitment and job performance were related with organizational justice. The result showed that job performance and organizational commitment have positive effects on organizational justice. Moreover, relation of three variables practices positive impact on organizational performance. It was concluded organizational commitment and job performance, that are necessary for organizational justice, are used on the school sector on satisfactory levels.